Proceeding of 3rd Libyan conference on Medical and Pharmaceutical Sciences 2019 - Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2019)
Welcome to the Libyan Conference on Medical and Pharmaceutical Sciences (LCMPS) in its third run this year. We are grateful to our generous host, University of Tripoli Alahlia, for their wonderful hospitality. We are also grateful to all the organizations who have made the launching of a Libyan Conference possible. We chose the theme “Promoting Research in Medical and Pharmaceutical fields in Libya” for this year with the hope of gathering scientific scholars from around the country, to share their knowledge and opinion about research. I want to take this opportunity to thank the Board, the Advisory members, the Group Chairs, and the steering committee members for generously offering their time and expertise. Dear friends, this year we come with more confident as our university being recognized by Quality assurance center - Ministry of Higher education. We have expanded our cooperation with various scientific organizations, and professionals to share with us the most significant advances in our profession. Our gathering is a microcosm of Libyan scientist world. The members of most local universities are present here, in Janzur. The conference participants hail from around 20 institutes. Well, we hope that LCMPS is poised to become a reference conference and gold standard of Medical research in the country. Part of any gold standard is welcoming all participants with open arms and especially those whose voices have not always been able to reach a such gathering audience. May our joint efforts bring us closer together.